Modern potentials of prokinetics in treatment of gastroesophageal reflux disease - A. A. Sheptulin; V. A. Kiprianis (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To estimate up-to-date options and prospects of application of prokinetics in treatment of gastroesophageal reflux disease (GERD).Original positions. Nowadays proton pump inhibitors (PPI) are the basic drugs used in treatment of GERD. At the same time in last years cases of their inefficacy became frequent that can be caused by «night acid outbreak», and also non-acid refluxes. As GERD is diseases with primary disorders of motility of the esophagus and the stomach, in its treatment prokinetics (domperidone, itopride hydrochloride) can be applied.Conclusion. In the case of resistance of GERD prokinetics can be added to PPI treatment (itopride hydrochloride, domperidone).